Development of a Multi-Criteria Decision Support System for Scholarship Selection Based on the Analytical Hierarchy Process (AHP) Method - Fajri, Viranti; Anwar, Muhammad (Universitas Negeri Padang, 2021)
Ensuring fairness and consistency in scholarship selection remains a major challenge, particularly in institutions serving underprivileged students. Conventional decision-making methods are often subjective and lack standardized evaluation criteria, leading to inconsistent outcomes. This study proposes a web-based Decision Support System (DSS) integrated with the Analytic Hierarchy Process (AHP) to enhance the objectivity, transparency, and efficiency of scholarship selection. The AHP method enables stakeholders to perform structured pairwise comparisons of selection criteria, calculate consistency ratios, and generate priority weights to rank candidates objectively. The system was developed using PHP and MySQL, and designed via a modular MVC architecture. A case study involving 45 applicants across three vocational high schools in Padang, Indonesia, was conducted using five criteria: academic performance, parental income, number of dependents, extracurricular achievements, and student organization involvement. Evaluation results show that the system reduced processing time by 38%, improved ranking consistency, and increased stakeholder satisfaction based on survey feedback. The system’s centralized, web-based nature also facilitates data sharing between schools and education authorities. Despite its benefits, limitations include the use of static weight configurations and restricted institutional coverage. Future work will focus on incorporating adaptive decision models and expanding implementation across a wider educational context to support policy-driven flexibility.